Analisis Pengaruh Gambatan Gaya Gravitasi Melalui Parasut Sederhana - Silvi Mutia; Roslita Anggraeni; Yunda Wahyuning Tyas; Khalda Naila; Satria Firmansah; Yuni Ratna Sari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to analyze the effect of gravitational resistance on the motion of falling objects through the use of a simple parachute. The experiment was conducted by dropping objects with and without parachutes from the same height, then observing and comparing the movement patterns and characteristics of the falling objects. The method used is descriptive analysis to understand the mechanism and dynamics of air drag caused by a simple parachute. The results show that the use of a simple parachute can clearly slow down the free fall rate of the object and change its movement pattern. This is due to the air drag generated by the parachute opposing the force of gravity, thereby controlling and controlling the fall of the object. These findings provide a deep qualitative understanding of the role of parachutes in reducing the effects of gravity, which can be utilized in various applications, such as aircraft design, transportation equipment development, and other fields that require controlling the force of gravity.